IMPLEMENTASI PROGRAM KEMITRAAN DAN BINA LINGKUNGAN PT. TELKOM INDONESIA, TBK DIVISI REGIONAL V JAWA TIMUR KANTOR DAERAH TELEKOMUNIKASI SURABAYA BARAT PADA INDUSTRI TENUN SARUNG DI DESA WEDANI, KECAMATAN CERME – KABUPATEN GRESIK JAWA TIMUR - Risha Masruroh, Kristyan Dwijosusilo & (Master of Public Administration, Universitas Slamet Riyadi, 2019)
Dwijokosusilo; Masruroh, 2019. ?Implementation Of Partnership AndCommunity Development Program Pt. Telkom Indonesia, Tbk RegionalDivision V East Java Telecommunication Regional Office In WestSurabaya In Weaving Industry In The Village Of Wedani, CermeSubdistrict ? Gresik Regency East Java?. Public Administration, Dr.Soetomo University Surabaya.The Partnership and Community Development Program (PKBL) is aprogram to improve the ability of small businesses to become resilientand independent through the use of funds from the profits of state-ownedenterprises (BUMN). The obligation for BUMN is stated in the Ministerof State-Owned Enterprises Regulation Number 05 / MBU / 2007 whereBUMN are required to set aside 2% of their net profit for PKBL. Thisstudy wants to describe how the implementation of PKBL PT. TelkomIndonesia, Tbk Regional Division V East Java Regional Office ofTelecommunications (Kandatel) West Surabaya in Weaving GloveIndustry in Wedani Village, Cerme District, Gresik Regency, East Java.The methodology of this research is qualitative descriptive. The analysisof this study using the Merille S. Grindle policy implementation modelincludes process factors, achievement of policy objectives, publicsupport, resources, communication, implementer programs andcompliance-responsibility. The loan process runs smoothly because thefostered partners can fulfill the specified requirements but in the processof repayment the installments are not running smoothly. PKBL hassucceeded in achieving its stated goals despite its success varies amongthe fostered partners. Public support is shown by the number of fosteredpartners applying for capital loans with consideration of low interest,flexible requirements and there are various programs to help themsucceed in achieving their business goals. Resources from PT. Telkomhas worked optimally because it has carried out socialization, assistance,monitoring and guidance so that a maximum of 100 million loans aresufficiently absorbed by the trained partners with a variety of loans.Communication has been carried out continuously to obtain measures ofachievement of results and levels of satisfaction. The implementation program continues to be carried out quite a lot, not only soft loanassistance, but also followed by online marketing techniques, training onwebsite marketing for woven sarong products, and facilitatingparticipation in home industry product craft exhibitions, management ofwoven glove cooperatives in Wedani village, and internet networkinstallation. . For compliance and response factors, the assisted partnersin general have carried out all obligations even though they cannot bemaximized and still need to be improved in the future.Keywords : Implementation, Partnership & Community Development Program,Weaving Gloves, PT. Telkom